2010
DOI: 10.1097/paf.0b013e3181e12eb8
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Issues in Cases of Water Birth Fatalities

Abstract: Birth under water has become a widely disseminated technique that is promoted to improve the quality of labor. The case of a 42-week gestation male infant is reported who died of respiratory and multiorgan failure secondary to florid pneumonia and sepsis due Pseudomonas aeruginosa following a water birth. Other infants who have been delivered underwater have drowned or have had near-drowning episodes with significant hyponatremia and water intoxication. Local and disseminated sepsis has been reported, with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
0
17
0
3
Order By: Relevance
“…Although these risks are similar to the ones found during normal vaginal deliveries, the immersion factor might be responsible to the negative interest many times attributed to water birth (Byard & Zuccollo, 2010).…”
Section: Introductionmentioning
confidence: 84%
“…Although these risks are similar to the ones found during normal vaginal deliveries, the immersion factor might be responsible to the negative interest many times attributed to water birth (Byard & Zuccollo, 2010).…”
Section: Introductionmentioning
confidence: 84%
“…Wiąże się również z większym zadowoleniem kobiet w czasie takiego porodu w porównaniu z porodem tradycyjnym [2,7]. are a number of studies indicating the risk of infection, thermoregulatory disorders, respiratory distress and perinatal hypoxia in neonates born in water [10,11,12,13]. The possibility of pulmonary aspiration of water is also concerning [9].…”
Section: W St ę Punclassified
“…The frequency of resuscitation after birth and the necessity of Ostatnio opublikowany raport amerykańskich pediatrów i położników kwestionuje jednakże korzyści pły-nące z takiego porodu dla noworodków [9]. Istnieją również liczne badania wskazujące na ryzyko wystą-pienia infekcji, zaburzeń termoregulacji, zaburzeń oddychania, niedotlenienia okołoporodowego u noworodków po porodzie wodnym [10,11,12,13]. Dyskutowana jest także możliwość aspiracji wody przez dziecko [9].…”
Section: Mat E Ri Al An D Me T H Od Sunclassified
“…Subsequently, a study by Byard and Zuccollo reported 4 cases of severe respiratory distress in neonates after water birth, 1 of whom died of overwhelming sepsis from Pseudomonas aeruginosa. 19 Although it has been claimed that neonates delivered into the water do not breathe, gasp, or swallow water because of the protective "diving reflex," studies in experimental animals and a vast body of literature from meconium aspiration syndrome demonstrate that, in compromised fetuses and neonates, the diving reflex is overridden, 27,28 which leads potentially to gasping and aspiration of the surrounding fluid.…”
Section: Reported Complications From Immersion During Labor and Deliverymentioning
confidence: 99%
“…Individual case reports and case series have noted complications for the mother and the neonate [17][18][19][20][21][22][23][24][25] that highlight potential risks from immersion during labor and delivery. Because the denominators are not uniformly reported, the exact incidence of complications is difficult to assess.…”
Section: Reported Complications From Immersion During Labor and Deliverymentioning
confidence: 99%